Commercial law including company law and industrial law - Sen, Arun Kumar; Mitra, Jitendra Kumar (Kolkata : The World Press, 2001)
Business
Keywords: Commercial law; Industrial law; Business law; Company law; Arbitration; Securities; Consumer protection act